Description Between Cats Exposure with Toxoplasmosis Disease on Cats Owner and Not- Cats Owner in Mulyorejo Subdistrict, Surabaya City - Prayuani Dwi Agustin; J Mukono (Universitas Airlangga, 2015)
Abstract: Toxoplasmosis is an infectious disease caused by Toxoplasma gondii that transmitted from animals to humans. Actually, the symptoms of toxoplasmosis are asymptomatic with non-spesific and similar to other diseases. Cats are definite host of Toxoplasma gondii. The feces from infected cat contains million oocysts and infective to humans. Detection of toxoplasmosis in human can be done with a serological test to see the levels of immunoglobulin M (IgM) and immunoglobulin G (IgG) anti-toxoplasmosis. The purpose of this study was to identification toxoplasmosis and describe between exposure from cats with toxoplasmosis disease to people who own and don't own cats in Mulyorejo Subdistrict, Surabaya City. This study was an descriptive observational research with cross sectional design in two populations. The subject was choosen randomly. This study was done to 25 respondents as cat owner and 25 respondents who weren't. Data was collected from questionnaire and respondent's blood sample. Prevalence of toxoplasmosis in cat owner 52% and 48% in not-cat owner. Crosstabulation showed that there were similar tendency between variables of feral cats, number of feral cats, and presence of cat's feces to toxoplasmosis disease on cats owner and not-cats owner in Mulyorejo Subdistrict, Surabaya City.It is expected that the community is able to notice the presence of feral cats and cat's feces around it to avoid the risk of infection from Toxoplama gondii.Keywords: Cats owner, Not-cats owner, Cat, Toxoplasmosis